2014
DOI: 10.1097/cad.0000000000000012
|View full text |Cite
|
Sign up to set email alerts
|

Oxymatrine induces apoptosis in human cervical cancer cells through guanine nucleotide depletion

Abstract: Oxymatrine is an alkaloid obtained primarily from Sophora roots and has been shown to show anticancer effects in various cancers. However, the cellular and molecular effects of this agent on cervical cancer have been poorly characterized. Here, we investigated the antitumor effect of oxymatrine on a human cervical cancer cell line (HeLa). Our results showed that application of oxymatrine significantly inhibited the cell growth and tumorigenesis in a dose-dependent manner and induced apoptosis through caspase-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 17 publications
1
34
0
Order By: Relevance
“…Oxymatrine treatment significantly induces apoptosis by increasing Bax protein expression and reducing Bcl-2 in human lung cancer A549 cells [53]. Proteomic analysis has shown that oxymatrine induces apoptosis in HeLa cells by inhibiting inosine monophosphate dehydrogenase type II (IMPDH2), mitochondrial related apoptotic protein [54]. These studies suggest that oxymatrine may be a useful drug candidate for cancer therapy.…”
Section: Traditional Chinese Medicines (Tcms) As Anti-cancer Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxymatrine treatment significantly induces apoptosis by increasing Bax protein expression and reducing Bcl-2 in human lung cancer A549 cells [53]. Proteomic analysis has shown that oxymatrine induces apoptosis in HeLa cells by inhibiting inosine monophosphate dehydrogenase type II (IMPDH2), mitochondrial related apoptotic protein [54]. These studies suggest that oxymatrine may be a useful drug candidate for cancer therapy.…”
Section: Traditional Chinese Medicines (Tcms) As Anti-cancer Agentsmentioning
confidence: 99%
“…20( S )-Ginsenoside Rg3 (saponins) chemosensitizes vincristine, doxorubicin, etoposide, and colchicine resistant KBV20 cell lines in a time- and dose-dependent manner [11]. Oxymatrine chemosensitizes cisplatin resistant HeLa/DDP cells by suppressing inosine monophosphate dehydrogenase type II (IMPDH2) levels and inducing apoptosis through the mitochondrial pathway [54]. CKI may also act as a stimulator of drug resistance reversal and chemosensitization in cancer.…”
Section: Chemoresistance In Cancer and Chemosensitization By Naturmentioning
confidence: 99%
“…In vivo tumorigenicity was done as previously described [12]. In brief suspensions of tumor cells HT29 (1 Â 10 6 viable cells/mouse) were implanted into the right flank region of BALB/c nude mice.…”
Section: Animal and Tumor Xenograft Assaysmentioning
confidence: 99%
“…Although the antitumor activities of OMT have been observed in various tumors181920212223243839, there are no reports regarding the effects of OMT on human synovial sarcoma. In this study, we found that OMT inhibited the viability of SW982 cells in a time- and dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%